IEEE GLOBECOM 2008 - 2008 IEEE Global Telecommunications Conference 2008
DOI: 10.1109/glocom.2008.ecp.904
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Access Outerbounds and the Inseparability of Parallel Interference Channels

Abstract: Abstract-It is known that the capacity of parallel (multi-carrier) Gaussian point-to-point, multiple access and broadcast channels can be achieved by separate encoding for each subchannel (carrier) subject to a power allocation across carriers. In this paper we show that such a separation does not apply to parallel Gaussian interference channels in general. A counter-example is provided in the form of a 3 user interference channel where separate encoding can only achieve a sum capacity of log(SNR)+o(log(SNR)) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…In a subsequent work, Host-Madsen and Nosratinia [9] showed that the sum-rate multiplexing gain of a K user SISO IFC-GF cannot exceed K/2. Cadambe and Jafar [14] showed that a sum-rate multiplexing gain of K/2 is actually achievable in ergodic timevarying fully-connected IFCs, even without user cooperation, by a transmission technique named interference alignment. Recently, Prabhakaran and Viswanath in [15] derived the sumrate multiplexing gain of the high-SNR deterministic approximation of a Gaussian IFC-GF for fully symmetric networks.…”
Section: Introductionmentioning
confidence: 99%
“…In a subsequent work, Host-Madsen and Nosratinia [9] showed that the sum-rate multiplexing gain of a K user SISO IFC-GF cannot exceed K/2. Cadambe and Jafar [14] showed that a sum-rate multiplexing gain of K/2 is actually achievable in ergodic timevarying fully-connected IFCs, even without user cooperation, by a transmission technique named interference alignment. Recently, Prabhakaran and Viswanath in [15] derived the sumrate multiplexing gain of the high-SNR deterministic approximation of a Gaussian IFC-GF for fully symmetric networks.…”
Section: Introductionmentioning
confidence: 99%
“…One also has to deal with the fact that parallel interference channels are inseparable [4], [5]. That is, one cannot separately code for each channel instances and simply allocate power across these codes.…”
Section: Introductionmentioning
confidence: 99%
“…This was subsequently used in the DOF analysis for the two user X channel in [5], [6]. Recent works that consider the DOF of wireless networks under different network settings include [7]- [10]. Outer bounds on the DOF were derived in [11] and [12].…”
Section: Introductionmentioning
confidence: 99%